Hubungan Pengetahuan dan Sikap Petani terhadap Penerapan Pupuk Organik pada Usahatani Kopi di Subak-Abian Wanasari Kenjung Desa Catur Kecamatan Kintamani Bangli - NYOMAN PASEK SURYA PREMANA; I DEWA GEDE RAKA SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
The Correlation between Farmers' Knowledge and Attitudes with the Application of Organic Fertilizer in Coffee Farming at Subak-abian of Wanasari Kenjung , Catur Village, Kintamani Sub-District, Bangli Regency The use of organic fertilizers on many farms has a positive impact, including on coffee farming. Knowledge, attitudes, and application of farmers about good organic fertilizer is the key to the success of coffee farming.This study aims to determine the level of knowledge, attitudes of farmers and application and their relationship in the use of organic fertilizers in coffee plants in the Subak-abian of Wanasari Kenjung of Catur Village, Kintamani Sub-District, Bangli Regency. Sampling was carried out by Simple Random Sampling method. Data analysis methods used were descriptive analysis and Spearman Rank correlation analysis.Descriptive analysis results show that farmers' knowledge of organic fertilizer is in the good category with a total score of 1,252, while the attitude of farmers is in the category of strongly agreeing with a total score of 1,667, and the application of farmers is in the quite good category with a total score of 876. The results of Spearman Rank correlation analysis show there is a strong relationship between knowledge and attitude with a correlation value of 0.556 **. Knowledge and application also have a strong relationship with a correlation value of 0.528 **. There is no relationship between attitude and application with the resulting correlation value of 0,315 with a significant value of 0,062> 0,05.